Essence of partnership management in project-based learning: Insights from a university’s global project programme - PAN, Gary (Institutional Knowledge at Singapore Management University, 2021)
Universities today are embracing teaching pedagogy of project-based learning (PBL) through collaboration with industry. PBL allows students to learn theory in the classroom, then apply what they have learned in the field, solving a wide array of business or societal challenges facing organizations, while at the same time, solidifying their own knowledge. While there are many benefits of such academic-industry partnership, there are also challenges that if not addressed, may have serious consequences. This study aims to develop a framework that highlights the essence of partnership management in a PBL setting and validate the framework by conducting a focus group study on a university in Singapore’s PBL programmes called UNIS-X and UNIS-XO. Our results suggest that the key features of partnership management include value proposition, depth of collaboration, knowledge creation and exchange, and continuous feedback. Our findings offer useful insights to managing effective partnership when engaging industry partners in a PBL programme. With this knowledge, educators can devise useful actions to ensure these features of partnership are established and maintained throughout a PBL course. Implications for research and education relating to PBL with an industry focus are highlighted.